Influencia de las estrategias activas en el proceso enseñanza aprendizaje del área de lengua y literatura de los estudiantes de octavo grado paralelos a, b, c de educación general básica del colegio nacional en “Ciencias Juan Montalvo” de la ciudad de Machala, provincia de El Oro, periodo lectivo 2014-2015 - Guevara Pando, Paola Elizabeth (2015)
Nowadays the education has gone through transitional stages of innovation looking for an education of quality, with the active participation of students in the teaching-learning process through which new knowledge that allow transforming in experiences of everyday life will be found.